REKONSTRUKSI NAMA PAPUA DAN IRIAN DALAM LINTASAN SEJARAH - Burdam, Yohanes; Winoto, Darmawan Edi; Rahman, Eka Yuliana (UNIVERSITAS RIAU KEPULAUAN, 2020)
This study attempts to reconstruct the use of the names Papua and Irian in the Indonesian Historical Path; and describe the dynamics of local struggle and the role of intellectuals before and after Indonesia's independence in interacting with the Republic of Indonesia (NKRI). The research uses a structuralism approach from Christopher Lloyd (1988), historical methods from Marc Bloch (1988), and the